Condições de segurança em um laboratório acadêmico do Departamento de Química da UFSCar: análise diagnóstica e proposta de um Manual para procedimentos seguros - Uliana, Cezar Augusto (2020)
Academic Laboratories are a source of concern due to the risks inherent in the activities carried out on their premises. In general, the handling of chemical products of different classes occurs, the handling of equipment that operates under intense pressure, heat or cold, equipment that generates noise at high levels or with heated surfaces and exposed rotating parts. It is reasonable to assume that students in the initial cycles are unaware of the potential risks to which they will be exposed during laboratory classes. Eventually, the conditions for handling products and operating equipment can be aggravated due to other factors such as, for example, the construction characteristics of the environments. With the application of the case study method and the exploratory observation methodology, they were observed during classes at an Academic Laboratory of the Department of Chemistry (DQ) of the Federal University of São Carlos (UFSCar) - São Carlos campus, their constructive, operational and organizational, and also the 'user actions', entitled 'student risk actions', characterized in two aspects: accident risk and health risk, and the observations registered occurrences of both aspects. With the monitoring and study of the routine of the laboratory associated with the moment of the class, a diagnosis is made that allows, in an initial moment, the elaboration of the orientative material, this being a first step for the subsequent elaboration and implantation of specific manuals by the academic laboratory. , given the particularities of each one, in order to reduce the risks related to the health and safety of its users, that is, those who work there or who develop activities, especially students. Considering the many activities developed in academic laboratories in various departments at UFSCar, it became evident that this theme and its application are extensible to conceptually similar work environments, in all campuses, as it was found the need for prior guidance to space users studied, which encouraged the elaboration of a Manual for Safe Procedures, the result of this research.